PENGARUH KEPEMIMPINAN PEREMPUAN TERHADAP KINERJA KEUANGAN PERUSAHAAN (Studi pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia (BEI) Tahun 2020-2024) - Adinda Putri Maelangkey; Siti Mutmainah (Diponegoro Journal of Accounting, 2026)
This study aims to examine the influence of female leadership on financial performance in banking companies listed on the Indonesia Stock Exchange (IDX) during the 2020-2024 period. The dependent variable in this study is the financial performance of banking companies. The variables studied include women on the board of commissioners and women on the board of directors. This study used a sample of 100 from 47 banking companies listed on the Indonesia Stock Exchange (IDX). The sample was selected using a purposive sampling method. The data used were secondary data obtained from the banking companies' annual reports and met the required criteria for this study. The company's financial performance measurement used as the dependent variable was Return on Assets (ROA). Hypothesis testing in this study used multiple regression analysis. The results of this study indicate that the proportion of women on the board of commissioners has a positive and significant effect on company financial performance. Meanwhile, the proportion of women on the board of directors has no significant effect on company financial performance.